"Today I Tell" A Comics and Story Creation App for People with Autism Spectrum Condition. Issue 8 (9th May 2019) - Martin, Estefania; Cupeiro, Carlos; Pizarro, Laura; Roldán-Álvarez, David; Montero-de-Espinosa, Guadalupe
ABSTRACT: This article describes the design, development, and evaluation of an application to help people with autism spectrum condition (ASC) express themselves through the creation of stories and comics. The intended platform of the application is touchscreen devices. The design process follows a human-centered design approach involving caregivers, teachers, usability experts, primary school students, and people with ASC. The characteristics considered are explained to design and implement the application, as well as the different evaluation steps. The prototype design was evaluated with 36 experts (teachers, caregivers, and usability experts). Next, 14 primary school students and 10 participants from a special education institution tested the application. Among all the participants, five students of the primary school institution have attention-deficit hyperactivity disorder and five students of the special education institution had ASC. The feedback gathered shows the importance of multidisciplinary teams in developing an application aimed at people with special needs. Non-functional features such as usability and accessibility can be bypassed by developers and this is the point at which teachers, caregivers, usability experts, and even the end users of the application can provide their insights in order to improve the product during its development phase. This also reduces the costs that would be incurred if the final product had to be changed after its development.